High‐grade malignant transformation of a radiation‐naïve nasopharyngeal angiofibroma. (3rd February 2016) - Allensworth, Jordan J.; Troob, Scott H.; Lanciault, Christian; Andersen, Peter E.
Abstract: Background: Nasopharyngeal angiofibromas are typically considered benign vascular neoplasms, with descriptions of high‐grade sarcomatous change found only in lesions with prior radiotherapy. Methods and Results: We describe the first reported case of high‐grade malignant change in a nasopharyngeal angiofibroma naive to radiation. A 45‐year‐old man presented with left‐sided nasal congestion and fullness and was found to have a left‐sided nasopharyngeal mass with intracranial extension on CT scan. A biopsy of the mass revealed nasopharyngeal angiofibroma. The patient opted for MRI surveillance, which revealed interval growth 3 years later. Decompression surgery revealed only angiofibroma, but resection 9 months later demonstrated high‐grade sarcoma and concomitant angiofibroma. The patient had residual disease which progressed through chemoradiation, and is now pursuing clinical trial enrollment. Conclusion: Malignant transformation of nasopharyngeal angiofibroma is extremely rare. As highlighted by this report, high‐grade undifferentiated lesions may arise in tumors without previous radiation. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2425–E2427, 2016